Potential drug-drug interactions and associated factors among hospitalized pediatric patients in Adigrat general hospital, Tigrai, north Ethiopia: a retrospective cross-sectional study - Gebretekle Gebremichael Hailesilase; Abrahaley Mulu Kidane; Haylay Araya Gebrezgabiher (BMC, 2024)
Abstract Background Drug-drug interactions (DDIs) are associated with increased or decreased adverse effects and decreased or decreased therapeutic effects. Hospitalized pediatric patients are exposed to a number of potential DDIs (pDDIs). There are limited studies on pDDIs among pediatric patients in Ethiopia. This study was aimed to evaluate the pDDIs and associated factors among hospitalized pediatric patients in Adigrat general hospital, Tigrai, northern Ethiopia. Methods A retrospective cross-sectional study was carried out among hospitalized pediatric patients in Adigrat general hospital from 01 July 2020 to 31 August 2020. A simple random sampling technique was used to select medical charts. Micromedex 2.0 database was used to screen pDDIs. Data was analyzed using statistical package for social science version 21 and a P-value of ≤ 0.05 was considered statistically significant. Results Of the total 146 patients studied, 100 (68.5%) were exposed for at least one pDDI. A total of 158 pDDIs consisting of 33 distinct interacting drug pairs were identified. About 19.3% of the patients had at least one major pDDI, 6.7% at least one moderate and 68.9% at least one minor pDDIs. On the other hand, 63.3% of the total pDDIs were minor and 25.9% major while 3. 8% were contraindicated pDDIs with 15.2% fair and 81.6% good level of documentation. The overall mean duration of pDDIs exposure was about 4.9 (1-23) days. The frequently occurring potential clinical consequences of pDDIs comprised increased risk of QT-interval prolongation (10.1%), theophylline toxicity (5.1%), antiepileptic toxicity (5.1%) and formation of ceftriaxone calcium precipitates (3.8%). Infant/toddler age group (adjusted odds ratio [AOR] = 31.961, 95% CI: 1.117-914.528), number of diseases (AOR = 0.255, 95% CI: 0.069-0.939) and polypharmacy (AOR = 0.276, 95% CI: 0.091-0.838) were associated with pDDIs exposures. Conclusions A large number of pediatric patients were exposed to a various pDDIs. Age, number of diseases and polypharmacy predicted for the occurrence of pDDIs. Besides, the major severity pDDIs encounted frequently in the current study can potentially lead to a life threatening cardio-vascular toxicicty from QT-interval prolongation. Clinicians should be vigilant to pDDIs to prevent potential clinical consequences of pDDIs. Moreover, computerized drug interaction screening and clincal pharmacy services should be practiced to improve patients' safety.